2015
DOI: 10.1039/c5ra23480h
|View full text |Cite
|
Sign up to set email alerts
|

Influence of photoactivated tetra sulphonatophenyl porphyrin and TiO2nanowhiskers on rheumatoid arthritis infected bone marrow stem cell proliferation in vitro and oxidative stress biomarkers in vivo

Abstract: Besides the lethal effects of photodynamic therapy on neoplasms, herein we report photoactivated TSPP–TiO2nanocomposites' growth promoting effect on rheumatoid arthritis BMS cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Biocompatible magnetic fluids consist of ferrite nanoparticles dispersed as a magnetic colloid that may also be used for local magnetic hyperthermia therapy (HPT). , HPT uses an external alternating magnetic field to promote an increase in local temperature (∼42–44 °C) and then cause the preferential destruction of cells and tissues. Recently, it has been suggested that the combination of porphyrins with nanocomposites could potentially be used as diagnostic and/or therapeutic agents for tumors and other diseases. , Nowostawska et al synthesized a new multimodal (magnetic and fluorescent) porphyrin-magnetite nanoconjugate for biological imaging. Zhao et al. used a new nanocomposite of TPPS porphyrin with TiO 2 nanowhiskers as effective bioimaging and photodynamic therapeutic agents for rheumatoid arthritis theranostics. Besides, TPPS encapsulated into the ZnO nanomaterials have increased the generation of singlet oxygen and the photobactericidal activity of ZnO nanorods …”
Section: Introductionmentioning
confidence: 99%
“…Biocompatible magnetic fluids consist of ferrite nanoparticles dispersed as a magnetic colloid that may also be used for local magnetic hyperthermia therapy (HPT). , HPT uses an external alternating magnetic field to promote an increase in local temperature (∼42–44 °C) and then cause the preferential destruction of cells and tissues. Recently, it has been suggested that the combination of porphyrins with nanocomposites could potentially be used as diagnostic and/or therapeutic agents for tumors and other diseases. , Nowostawska et al synthesized a new multimodal (magnetic and fluorescent) porphyrin-magnetite nanoconjugate for biological imaging. Zhao et al. used a new nanocomposite of TPPS porphyrin with TiO 2 nanowhiskers as effective bioimaging and photodynamic therapeutic agents for rheumatoid arthritis theranostics. Besides, TPPS encapsulated into the ZnO nanomaterials have increased the generation of singlet oxygen and the photobactericidal activity of ZnO nanorods …”
Section: Introductionmentioning
confidence: 99%
“…TSPP enters the cell via endocytosis and localizes in cellular organelle (lysosomes, endosomes, and endoplasmic reticulum) where it interferes with cellular signal pathways, thus producing apoptosis or necrosis (Høgset et al 2004 ; Berg et al 2011 ). Rehman et al ( 2015 , 2016b ) studied the protective effect of TiO 2 nanowhiskers (TiO 2 NWs)–TSPP complex in vitro and in vivo. TSPP–TiO 2 NWs were prepared by mixing TSPP and TiO 2 together.…”
Section: Titanium Dioxide Nanoparticles (Tio 2 Npsmentioning
confidence: 99%
“…During autoimmune diseases, such as RA, an altered functionality of autoimmune cells (B lymphocytes) may also influence the adjacent cells. 43 Hence, the bone marrow microenvironment is affected, leading to altered physiology and functionality of bone that ultimately leads to bone erosion and associated conditions.…”
Section: Introductionmentioning
confidence: 99%